Expression of Olfactory Sense-Related Genes in Chicken Olfactory Epithelium - Kazushi Koyama; Fuminori Kawabata (The Journal of Poultry Science)
Olfaction plays a key role in the selection and acquisition of feed as well as its vision and gustation. Although olfactory behavior in chickens is speculated to depend on olfactory receptors, trace-amine-associated receptors (TAARs), and its signaling pathway, insufficient information is available regarding the expression of these molecules in chicken olfactory epithelium. Here, we investigated whether genes encoding representative olfactory receptors, TAARs, and olfactory signaling pathway molecules were expressed in this tissue. Based on real-time quantitative polymerase chain reaction and agarose gel electrophoresis, we confirmed the expression of 18 olfactory receptors, three TAARs, and six signaling pathway genes, suggesting that chickens possess molecular mechanisms for capturing odorants and transducing olfactory signals.